Application of return measure method in research of calibration device for instrument of penetration resistance. (December 2021) - Ren, Xiang; Lu, Jinyu; Wang, Zhenyu; Huang, Weijun
Abstract: Instrument of Penetration resistance calibration device research based on the instrument's structure, working principle and JJF1372-2012 "Calibration Specification for Instrument of Testing Mortar-strength by Penetration Resistance Method" requirements, which was developed to automatically measure the force and the spring compress distance. Moreover, the calibration device can also obtain the penetration force in actual use through the return calibration method.